Peningkatan Nilai Tambah Limbah Peternakan Sapi melalui Produksi Pupuk Organik Berkualitas dan Bernilai Ekonomi - Elok kurnia novita Sari; Dimas Triardianto; Adhima Adhamatika; Shinta Widyaningtyas; Annisa'u Choirun (Insan Kreasi Media, 2026)
Sumberwaru Village, Jember Regency, is one of the major cattle-farming areas with a relatively large livestock population. However, cattle manure management remains inadequate. Most manure is left to accumulate around livestock sheds, generating unpleasant odors and posing environmental pollution risks, while a portion is discharged into irrigation channels, potentially degrading environmental quality. This community service program involved 25 members of a farmer group as target beneficiaries and aimed to increase the value of cattle manure through the production of high-quality organic fertilizer. The methods employed included educational outreach, technical training, and participatory mentoring, accompanied by evaluations using pre-test and post-test assessments as well as quality testing of the produced fertilizer. The results demonstrated that the participating farmer group members were able to understand and apply manure-processing techniques for organic fertilizer production. The resulting organic fertilizer met the required quality standards, with a C/N ratio of 18.4, a pH value of 7.2, and nitrogen (N), phosphorus (P), and potassium (K) contents that satisfied the minimum criteria for organic fertilizers. In addition to transforming livestock waste into a value-added product with economic potential, the program contributed to reducing environmental pollution and promoting sustainable agricultural practices.